2016
DOI: 10.1016/j.im.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Value co-creation between firms and customers: The role of big data-based cooperative assets

Abstract: A B S T R A C TTo better understand how big data interconnects firms and customers in promoting value co-creation, we propose a theoretical framework of big data-based cooperative assets based on evidence of multiple case studies. We identify four types of big data resources and four types of associated digital platforms, and we explore how firms develop the cooperative assets by transforming big data resources via the theoretical lens of service-dominant logic. This study offers a new theoretical perspective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
181
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(185 citation statements)
references
References 61 publications
(119 reference statements)
2
181
0
2
Order By: Relevance
“…Communication platforms support participants group communication, sharing and opinion expressions, such as social media, including Facebook and WeChat [19]. Participative platforms attract customers to participate actively in product improvement and to configure new service or business decision with the company together, for example, a company motivate and invite customers to participate in new product R&D [25].…”
Section: Mobile Platformmentioning
confidence: 99%
See 1 more Smart Citation
“…Communication platforms support participants group communication, sharing and opinion expressions, such as social media, including Facebook and WeChat [19]. Participative platforms attract customers to participate actively in product improvement and to configure new service or business decision with the company together, for example, a company motivate and invite customers to participate in new product R&D [25].…”
Section: Mobile Platformmentioning
confidence: 99%
“…Nowadays, the mobile platform, with its advantages of low cost, portability, and connectivity, is believed to give a great chance to narrow all political, social participation and economic divide and achieve related social inclusion [23,24]. Through connecting multi-actors and integrating different resources [18,19], the mobile platform can enhance transactional efficiency [25], facilitate interactions [26] and promote community building [27]. Studies have shown that mobile platform not only eliminates digital divide, but also play a vital role in communication and social participation.…”
Section: Introductionmentioning
confidence: 99%
“…Social media technologies significantly reinforce individual customers' utilization of social networking resources, promote inter-group interactions, and enhance the interpersonal influence, thus giving rise to consumer empowerment [18,21]. The diversity of resources owned by individual customer determines his/her influence within the social network and the value to engagement [37]. In this study, we focused on customer engagement in marketing and divide customers into two general categories: exceptional customers who own heterogeneous personal resources that differ from firm-owned, thus showing significant influence on other customers' purchasing decisions, and average customers who are susceptible to others rather than influencing others.…”
Section: Empowerment and Exceptional Customersmentioning
confidence: 99%
“…2.1 SERVICE STANDARDIZATION VERSUS UNIQUENESS Each service transaction may result in a particular set of circumstances, either in response to a specific client problem or as a result of production on demand (Gallouj and Weinstein, 1997a). In addition, high degrees of interaction with clients can lead to the development of customized products (Xie et al, 2016;Vence and Trigo, 2009a). The chances of improving efficiency through codification, so as to achieve standardization, are reduced where "bespoke service provision" exists (Bettiol et al, 2012) or where it is unlikely the customer's problem will be repeated (Sundbo, 1997).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…There is more interaction and feedback from customers in services than in manufacturing (Kindstrom and Kowalkowski, 2009), and likely this has been partly driven by value creation from big data in the digital age (Xie et al, 2016). The degree of interaction between service provider and client has been identified as a key difference between services and manufacturing activities (Burton, 2017;Gallouj and Weinstein, 1997a) contributing to successful innovation in services (Alam, 2006;Sundbo, 1997) and improving service-firm performance (Salunke et al, 2013;Agarwal and Selen, 2009;Carbonell et al, 2009;Frambach et al, 1998;Haliday and Troth, 2010;, Melton and Hartline, 2010).…”
Section: Customer-provider Interactionmentioning
confidence: 99%